Identification of Fusarium cf. Verticillioides as The Causal Agent of Pokka Boheng Disease in Sugarcane in the Department of Antioquia, Colombia (2018)
The cultivation of sugarcane represents an important part in the Colombian economy due to the diverse applications in industries like liquor, food, paper and biofuels. Sugarcane worldwide production is affected by the presence of phytopathogenic agents, mainly filamentous fungi such as Physalospora tucumanensis (red rot disease) and Fusarium spp. To date in Colombia, Pokka boheng disease whose causal agent is the fungus Fusarium verticillioides, has not been reported, which is why it is necessary to identify appropriately this microorganism, responsible for losses in productivity and food contamination. In order to isolate and identify the infectious agent from symptomatic tissues, disinfection and culture in liquid and solid culture mediums were performed in malt extract (2%) and yeast extract (0.2%) both liquid and solid, for 7 days. After several replicates in agar plate, a purification was made along with a morphological characterization based on the shape and color of the mycelium, as well as the type of spores generated. Additionally, the genetic material was extracted and gene markers (ITS, Elongation Factor 1-α (EF) and β-Tubulin (Btub)) were amplified by PCR. Then, DNA sequencing was used to obtain the data to make a phylogenetic reconstruction by probabilistic methods (Maximum Likelihood and Bayesian Inference). The isolated strain, named as EA-FP0013 was located in the Fujikuroi complex group, with high probable identity to Fusarium verticillioides. Thus, early and species-specific identification of these fungal isolates by molecular methods may allow the timely diagnosis of emerging pathophysiological diseases of interest in the region, and thus propose the respective control strategies.